Analysis of Phenolic Content, Flavonoids, and α-Amylase Enzyme Inhibition Activity of Ethanol Extracts and Clove Stem Fractions (Syzygium aromaticum L.) - Oktafia Nur Fatimah; Niken Luthfiyanti; Danang Raharjo (CV. AFDIFAL MAJU BERKAH, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia resulting from impaired insulin secretion, insulin action, or both. The condition is associated with severe long-term complications, including cardiovascular disease, nephropathy, neuropathy, and retinopathy, making effective management strategies crucial. One therapeutic approach is the inhibition of the α-amylase enzyme, which plays a key role in the hydrolysis of complex carbohydrates into glucose, thereby controlling postprandial blood sugar levels. Natural products containing bioactive compounds such as phenolics and flavonoids are increasingly being investigated as safer alternatives to synthetic drugs. Clove stalks (Syzygium aromaticum L.), an underutilized byproduct of the clove plant, are known to be rich in these compounds and may serve as a potential natural enzyme inhibitor. This study aimed to analyze the phenolic and flavonoid content as well as α-amylase inhibitory activity of ethanol extract and its fractions (n-hexane, ethyl acetate, and water) obtained from clove stalks. Extraction was carried out using maceration with 70% ethanol, followed by fractionation and analysis with UV-Vis spectrophotometry. The ethanol extract exhibited the highest phenolic and flavonoid levels (44.581 mg GAE/g and 50.491 mg QE/g, respectively), while the ethyl acetate fraction demonstrated the strongest α-amylase inhibitory activity with an IC₅₀ value of 26.303 µg/mL. These findings suggest that the ethyl acetate fraction of clove stalks has promising potential as a natural antidiabetic agent, supporting its development as an alternative functional ingredient in diabetes management.